Expression and DNA methylation of MET1, CMT3 and DRM2 during in vitro culture of Boesenbergia rotunda (L.) Mansf. - Karim, Rezaul; Tan, Yew Seong; Singh, Pooja; Nuruzzaman, Mohammed; Khalid, Norzulaani; Harikrishna, Jennifer Ann (College of Agriculture and Food Science, University of the Philippines Los Banos, 2018)
Somatic embryogenesis and plant regeneration are important developmental processes of in vitro culture, in which cells must undergo dedifferentiation, activation of cell division and reprograming of their metabolism, of their physiology and of their gene expression patterns. The processes of somatic embryogenesis and plant regeneration are also associated with changes in DNA methylation. In this study, the expression of METHYLTRANSFERASE 1, CHROMOMETHYLASE 3 and DOMAIN REARRANGED METHYLTRANSFERASE 2 was determined by Quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR) while the DNA methylation level was determined by Bisulfite sequencing of plant cells from meristematic block, embryogenic and non-embryogenic calli, prolonged cell suspension culture, ex vitro leaf and in vitro leaf of regenerated plants of Boesenbergia rotunda. We observed that the expression of DNA methyltransferase genes METHYLTRANSFERASE 1, CHROMOMETHYLASE 3 and DOMAIN REARRANGED METHYLTRANSFERASE 2 was the highest in meristematic block followed by embryogenic callus, and the lowest was in watery callus. DNA methylation at CG, CHG and CHH sequence contexts was observed to be generally lower in embryogenic callus than in other samples. We observed relatively higher expression levels and lower levels of DNA methylation at CG, CHG and CHH sequence contexts of MET1, CMT3 and DRM2 associated with somatic embryogenesis and regenerability in Boesenbergia rotunda.